The Role of Teachers in Classroom Management - Tiarani Mirela (Al-Alim: Jurnal Pendidikan Agama Islam, 2026)
Classroom management is a fundamental aspect in determining the quality of teaching and the success of students. Teachers play a central role as planners, organizers, and motivators in creating a learning environment that is conducive, effective, and efficient. This study employs a library research method by reviewing and analyzing relevant academic literature on classroom management. The findings indicate that classroom management is not universal, as each class has unique characteristics influenced by socio-economic background, socio-cultural context, learning habits, and available facilities. Teachers who are able to implement classroom management professionally can enhance students’ learning motivation, build communicative interactions, and foster a positive socio-emotional climate. Conversely, failure in classroom management has a direct impact on declining student achievement. Therefore, the role of teachers in classroom management is a crucial prerequisite for achieving educational goals, as the success of learning strongly depends on the teacher’s ability to design, organize, and motivate students effectively.